Altered Monocyte and Langerhans Cell Innate Immunity in Patients With Recurrent Respiratory Papillomatosis (RRP) - Israr, Mohd; DeVoti, James A.; Lam, Fung; Abramson, Allan L.; Steinberg, Bettie M.; Bonagura, Vincent R. (Frontiers in Immunology, 2020)
The micromilieu within respiratory papillomas supports persistent human papillomavirus (HPV) infection and disease recurrence in patients with recurrent respiratory papillomatosis (RRP). These patients show polarized (TH2-/Treg) adaptive immunity in papillomas and blood, enriched immature Langerhans cell (iLC) numbers, and overexpression of cyclooxygenase-2/prostaglandin E2 (PGE2) in the upper airway. Blood monocyte-derived, and tissue-derived iLCs from RRP patients and controls were now studied to more fully understand innate immune dysregulation in RRP. Patients' monocytes generated fewer iLCs than controls, due to a reduced fraction of classical monocytes that generated most but not all the iLCs. Prostaglandin E2, which was elevated in RRP plasma, reduced monocyte-iLC differentiation from controls to the levels of RRP patients, but had no effect on subsequent iLC maturation. Cytokine/chemokine responses by iLCs from papillomas, foreskin, and abdominal skin differed significantly. Freshly derived tissue iLCs expressed low CCL-1 and high CCL-20 mRNAs and were unresponsive to IL-36γ stimulation. Papilloma iLCs uniquely expressed IL-36γ at baseline and expressed CCL1 when cultured overnight outside their immunosuppressive microenvironment without additional stimulation. We conclude that monocyte/iLC innate immunity is impaired in RRP, in part due to increased PGE2 exposure in vivo. The immunosuppressive papilloma microenvironment likely alters iLC responses, and vice versa, supporting TH2-like/Treg HPV-specific adaptive immunity in RRP.